Multilayered-Amniotic Membrane Transplantation in Gunshot Powder Injury: A Case Report - Amanda, Nitia; Havriza Vitresia (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Background: Amniotic membrane transplantation has been widely used to repair various ocular surface conditions, including inflammatory, infectious, traumatic, and neoplastic conditions, with satisfactory results. a case of a 34-year-old male hit by a gunpowder explosion. Case presentation: We reported a case of a 34-year-old male hit by a gunpowder explosion. The right eye was hyperemic and felt blurry after the incident. On examination of the right eye, visual acuity was 20/150, and foreign bodies and erosion were found in the cornea. The patient planned to do foreign body extraction followed by a multilayered-amniotic membrane transplantation (ML-AMT) procedure. On the first and second day of follow-up, on the right eye, the visual acuity was 1/300, palpebral edema was decreased, and subconjunctival hemorrhage was found. On the cornea, there were ML-AMT and bandage contact lenses. Conclusion: Gunshot powder injury in the eyes is quite rare. The damage that can occur ranges from corneal epithelium abrasion to perforation and rupture of the eyeball. AMT has been successfully used in the management of eye trauma with defects on the ocular surface.